(untitled) (Parliamentary Studies, 2025)
The collection of documents, The Klaipėda Issue in Lithuanian Foreign Policy in 1919–1940, compiled and edited by Algimantas Kasparavičius, presents the Lithuanian state’s viewpoint, stance, and policy on the Klaipėda Region in a broad geopolitical context, extending the chronological boundaries of the subject (1923– 1939) that have prevailed until now. The initial chronological reference point is 1919, because by 1922 Lithuania had prepared the diplomatic and political ground for the annexation of the Klaipėda Region. The chronological end date of June 15, 1940 is based on Lithuania’s steady interest in the Klaipėda issue even after the loss of the region on March 22, 1939. The majority of the documents reveal the relations between Lithuania and Germany and communication with the signatory states of the Klaipėda Convention, Poland, and other states (Latvia, Estonia, Soviet Russia (after the end of 1922, the Soviet Union), Czechoslovakia, Finland, the United States of America, Turkey, Brazil, the Holy See, etc.). The collection contains almost 800 documents from the Ministry of Foreign Affairs Fund No. 383 and the Lithuanian Legation in London Fund No. 648 housed at the Lithuanian Central State Archives. The sources have been prepared in accordance with the principles of the science of historical sources.